Usual or unusual presentations of Dirofilaria repens in two sibling dogs: a case report - Barlozzari, Giulia; Felice, Tiziana; Salvato, Laura; Conti, Raffaella; De Liberato, Claudio; Furzi, Federica; Gabrielli, Simona; Scarpulla, Manuela (Parasitology research (1987), 2021)
This study describes two different manifestations of Dirofilaria repens infection in sibling dogs with microfilaremia. Dog 1, asymptomatic, harbored a gravid female of D. repens on the parietal layer of tunica vaginalis of one testicle and showed a marked circulating eosinophilia (3.3·10 3 /μL). Both testicles were normal in shape and size without any gross lesions. Dog 2 had a pyotraumatic dermatitis. The cases were confirmed by PCR and sequencing. The sequences obtained showed 100% identity with those of D. repens isolated from human scrotum in Croatia. The treatment with moxidectin 2.5% and imidacloprid 10%/kg was effective in eliminating microfilariae after just one application, as demonstrated by negative modified Knott’s tests and PCR analyses of blood samples. This status was maintained during the post-treatment observation period. The classical localization of D. repens in dogs is in subcutaneous tissues, within nodules or free; however, it can also occur with some frequency in testicles, as described in humans. The infection can be associated with circulating eosinophilia or pyotraumatic dermatitis, as reported in this study. Thus, in endemic areas, it is advisable to carefully inspect the removed testicles at neutering since parasite localization can take place without any macroscopic changes. Moreover, in the case of circulating eosinophilia or pyotraumatic dermatitis, investigations should include modified Knott’s test and PCR to ensure that D. repens is not the cause of these alterations. Rapid and sensitive tests for the early detection of infected animals would help to prevent or limit the spread of this zoonosis.